The Implementation of Collaborative Learning in Teaching English at a Junior Secondary School in Soppeng - Hamsah, Herlina; Noni, Nurdin; Sunra, La (International Journal of Contemporary Studies in Education, 2024)
The research explores the implementation of collaborative learning in teaching English at a Junior Secondary School in Soppeng. This research was conducted at SMP Neg. 1 Watansoppeng, focusing on the teacher's methods, challenges, and teacher’s perceptions of collaborative learning. It uses qualitative research to examine the teacher's strategies, challenges, and experiences in teaching English using this method. Interviews and observations were used to gain the data. The result of the data analysis showed that the teacher uses collaborative writing, peer tutoring, and consensus groups, allowing students to work together. However, challenges include time constraints, language proficiency issues, and managing group dynamics. The teacher views collaborative learning as an engaging approach that fosters creativity, independence, and problem-solving skills. The study suggests that teachers should monitor group dynamics and implement diverse strategies to improve English language instruction.